The Role of Librarian and the Transformation of Students’ Information Literacy Education: A Case Study at IAIN Curup - Jurianto; Hamzah, Syukri; Yulistio, Didi; Rizal, Syamsul; Wince, Eke; Sutriono, Sutriono; Syahril, Syahril (International Journal of Education Research and Development, 2025)
The development of information technology and the emergence of artificial intelligence (AI) have changed the way students’ access, assess, and utilize information in academic activities. In the Islamic Religious College (PTKI) environment such as IAIN Curup, this condition encourages the transformation of the role of librarians from technical implementers to academic partners and information literacy facilitators. This study aims to explore in depth how librarians carry out their educational role in improving student information literacy in the digital era. The method used is descriptive qualitative with a case study approach. Data were obtained through in-depth interviews, participant observation, and documentation, and analyzed using the Miles and Huberman model with validity maintained through triangulation and member checking. The theoretical framework used includes: The librarian’s guide to learning theory (Medaille, 2024), The research information’s theory (Walter & Wilder, 2022), and dynamic social interaction theory (Turner, 2023). The results of the study show that IAIN Curup librarians have functioned as digital information educators, academic partners, and institutional knowledge managers. However, this role has not been fully structured in institutional policies. Integration of information literacy into the curriculum, pedagogical training, and cross-role collaboration are needed. This study recommends strengthening librarian professionals through networks and Islamic scientific approaches such as tahqiq to form a reflective and ethical academic culture.